Integrating Physiology and Health Management in Practice Based On Islamic Medicine - Labib, Mohammad (AL-IMAM: Journal on Islamic Studies, Civilization and Learning Societies, 2025)
Physiology forms the scientific foundation of modern medicine, linking cellular mechanisms with systemic functions that sustain human life. In the context of contemporary healthcare, understanding physiological principles is not only essential for clinical decision-making but also for effective health management. This study explores the integration of physiological reasoning into health system governance, clinical protocols, and practice management. Through a systematic literature review, this paper examines how physiological understanding informs policies in resource allocation, technology adoption, and service delivery. The findings reveal that physiological literacy among healthcare leaders improves clinical efficiency, enhances patient safety, and supports rational health planning. Therefore, strengthening physiological education and its application in health management is crucial to building sustainable, effective, and patient-centered health systems.